DETERMINATION OF MINERAL AND TRACE ELEMENT IN SOME MEDICINAL PLANTS BY SPECTROSCOPIC METHOD - Ciftci, Harun; Caliskan, Cigdem E. R.; Erdogan Cakar, Ayse; Olcucu, Ali; Ramadan, Mohammed Sadeeq (YILDIZ TECHNICAL UNIV, 2020)
In this paper, the concentrations of elemental contents ((Macro mineral; calcium (Ca) and magnesium (Mg), trace elements; zinc (Zn), copper (Cu) and iron (Fe) and ultra-trace elements aluminum (Al), manganese (Mn), lead (Pb) and nickel (Ni) in some medicinal plants like dill (Anethum graveolens L.), clove (Syzygium aromatic-um), cardamom (Elettaria cardamomum), black mulberry (Morus nigra), oak gall (Quercus infectoria), camomile (Matricaria recutita L), basil (Ocimum basilicum), peppermint (Mentha x piperita), ginger (Zingiber officinale), purslane (Portulaca Oleracea L.), thyme (Thymus vulgaris L.) and cinnamon (Cinnamomum verum)) were determined with High Resolution Continuum Source Flame Atomic Absorption Spectrometer (HR CS-FAAS) by using the microwave digestion system. We found metal levels in investigating medicinal plants in the ranges: 0.18- 5.63 mg/g for Ca; 0.06- 1.37 mg/g for Mg; 0.01-0.03 mg/g for Al; 2.84 - 79.48 mu g/g for Zn; 2.77-74.38 mu g/g for Fe; 0.41 113.01 mu g/g for Pb; 0.13-0.54 mu g/g for Ni; 0.04 50.51 mu g/g for Mn and 0.01-5.97 mu g/g for Cu. The highest concentrations of the examined elements in the plants examined were found as follows: Ca in basil; Mg in purslane; Pb, Al and Zn in dill; Fe and Mg in ginger. Likewise, the lowest concentrations were found as follows: Pb in thyme; Zn in black mulberry; Cu in clove and Ni in cinnamon.
Keywords: Medicinal plant; microwave digestion; mineral; trace elements; METAL CONCENTRATIONS; HEAVY-METALS; HERBS; SPICES; Engineering